RECURRENCE PROFILE AND PROGNOSIS IN A NEGATIVE SENTINEL LYMPH NODE BREAST CANCER PATIENTS COHORT TREATED AT HOSPITAL DO SERVIDOR ESTADUAL DE SÃO PAULO - Vasconcelos, Raissa Naiara Alves Barros; Antonini, Marcelo; Cabral, Samira Marcondes; Cardoso, Mariana Soares; Solino, Matheus de Paula (Mastology, 2021)
Introduction: Breast cancer is the main cause of death by cancer among brazilian women and its incidence increases annually. Due to screening e new technologies, diagnosis without axillary metastasis is increasing. Objectives:This study aimed at evaluating locoregional recurrences, distant metastasis, prognostic factors associated to those outcomes and its impact on deaths among breast cancer patients treated in a public hospital of São Paulo. Methods: It is a retrospec- tive cohort study that included 342 T1-3N0 breast cancer patients with negative sentinel lymph node biopsy submitted to primary surgery between March 2014 and March 2019 at Hospital do Servidor Público Estadual (HSPE). Primary out - comes were locoregional recurrence rate, distant metastasis rate, mortality, disease free survival and overall survival. Secondary outcomes were the association between primary outcomes and prognostic factors established in the literature. Results: During 1.5 to 6.4 years of follow-up (median time 3.3 years), there was 3.8% locoregional recurrence cases, 4.1% distant metastasis and 3.8% deaths. Locoregional recurrence free survival in three years was 94.4% and metastasis free survival was 95.6%. Overall survival in three years was 97.2%. It was observed an association between locoregional recur- rence histological subtype and hormonal therapy, distant metastasis, histological subtype and tumor grade, deaths and tumor grade. The results evidence that locoregional recurrences increases distant metastasis, but do not reduce overall survival. On the other hand, distant metastasis decreases overall survival. Conclusions: This study showed that breast cancer patients without axillary metastasis treated at HSPE presentedconsistent locoregional recurrence, metastasis and mortality patterns in the literature. Further studies with more participants and longer follow-up are necessary to evaluate the relative risk of each prognostic factor included in the present research.